Prosodic Means of Speech Influence Realization: Auditory Analysis - Tomakhiv, Marta (East European Journal of Psycholinguistics, 2017)
The article offers the results of the experimental phonetics research on the role of intonation in speech influence realization in the video lecture as a main massive open online courses material. This methodology is elaborated according to the proven techniques in contemporary phonetics and combines the use of auditory analysis, methods of quantitative data and linguistic analysis, methods of semantic differential and questionnaire. The goal of the experiment was to prove the hypothesis about the role of prosodic organization and components of the tutors’ intonation in video lectures in better supporting students’ attention, capturing the interest to the subject, facilitating understanding, which help in realization of speech influence in scholarly discourse, thus making the communication and learning more efficient, productive and successful. As a result of the experiment, the intonation parameters used in the video lecture and contributory for students’ perception have been established. The paper gives brief insights into such notions as speech influence, scholarly discourse and an e-lecture as a genre of modern scholarly discourse.ReferencesАнтошинцева М. А. Механизмы адаптации жанра научно-учебной лекции кэлектронной сфере коммуникации. [Електронний ресурс]. Режим доступу:www.cyberleninka.ru/article/n/mehanizmy-adaptatsii-zhanra-nauchno-uchebnoy-lektsiik-elektronnoy-sfere-kommunikatsiiAntoshyntseva, M. A. Mekhanizmy adaptatsii zhanra nauchno-uchebnoy lektsii kelektronnoy sfere kommunikatsii. [Mechanisms of scientific and academic discoursegenre adaptation to the electronic domain of communication]. Retrieved from:www.cyberleninka.ru/article/n/mehanizmy-adaptatsii-zhanra-nauchno-uchebnoy-lektsiik-elektronnoy-sfere-kommunikatsiiВалігура О. Р. Фонетична інтерференція в англійському мовленні білінгвів:монографія. Тернопіль: Підручники і посібники, 2008.Valihura, O. R. (2008). Fonetychna Interferentsiia v Anhliiskomu Movlennia Bilinhviv.[Phonetical Interference in the English Speech of the Bilinguals]. Ternopil: Pidruchnykyi Posibnyky.Калита А. А. Энергетика речи: монография. К.: Кафедра, 2016.Kalyta, A. A. (2016). Energetika Rechi [Speech Energetics]. Kyiv: Kafedra.Калита А. А. Актуалізація емоційно-прагматичного потенціалу висловлення:монографія. Тернопіль: Підручники і посібники, 2007.Kalyta, A. A. (2007). Aktualizatsia Emotsiino-Prahmatychnoho Potentsialu Vyslovlennia.[Emotional and Pragmatic Potential of the Utterance Actualization]. Ternopil:Pidruchnyky i Posibnyky.Каспаринський О. Ф., Полянская Е. И. Видеолекция как жанр. [Електроннийресурс]. Режим доступу: https://istina.msu.ru/media/publications/articles/ 8e9/82a/3559014/29LINK_FOK13v07.pdfKasparinskyi, O. F., Polianskaia, E. I. Videolektsiia kak Zhanr. [Videolecture as aGenre]. Retrieved from: https://istina.msu.ru/media/publications/articles/8e9/т82a/3559014/29LINK_FOK13v07.pdf.Osgood, C. E., Suci, G. C. and Tannenbaum, P. H. (1957). The Measurement ofMeaning. Urbana, IL : University of Illinois Press.Падалка О. В. Просодика комунікативного членування промов сучаснихполітичних діячів Німеччини (експериментально-фонетичне дослідження):дисертація кандидата філологічних наук: 10.02.04 / Ольга Володимирівна Падалка.Київ: КНЛУ, 2015.Padalka, O. V. (2015). Prosodyka Komunikatyvnoho Chlenuvannia Promov SuchasnykhPolitychnukh Diiachiv Nimechchyny (Eksperymentalno-Fonetychne Doslidzhennia).Ph.D. dissertation [Prosody of the Communicative Segmentation of Speech ofContemporary German Politicians (Experimental Phonetics Research)]. Kyiv: KyivNational Linguistic University.Peer, W. Van, Hakemulder, F., Syngier, S. (2012). Scientific Methods for theHumanities. (Linguistic Approaches to Literature). Amsterdam: John Benjamins.Рубчак О. Б. Просодична організація англомовних інтерв’ю (експериментальнофонетичне дослідження): Дис. ... канд. філол. наук: 10.02.04. Київ: КНЛУ, 2015.Rubchak, O. B. (2015). Prosodychna Organizatsiia Anhlomovnykh Interviu(Eksperymentalno-Fonetychne Doslidzhennia). Ph.D. dissertation [Prosodic Structure ofthe English Interviews (Experimental Phonetics Research)]. Kyiv: Kyiv NationalLinguistic University.Седов К. Ф. Нейропсихолингвистика. Москва: Лабиринт, 2007.Sedov, K. F. (2007). Neiropsikholingvistika. [Neuropsycholinguistics]. Moscow:Labirint.Селіванова О. О. Мовленнєвий вплив у комунікативній взаємодії //Психолінгвістика. 2012. № 10. С. 223–229.Selivanova, O. (2012). Movlennievyi Vplyv u Komunikatyvnii Vzaiemodii.Psykholinhvistyka, 10, 223–229.Demetriadis, S., Pombortsis, A. E-Lectures for Flexible Learning: a Study on theirLearning Efficiency. Retrieved from: http://www.ifets.info/journals/10_2/13.pdfTomakhiv, M. (2016). E-Lecture as a new genre of scholarly discourse. Science andEducation a New Dimension. Philology, IV (23), 100, 80–83.Trench Brian. Internet − turning science communication inside‐out? Retrieved from:http://doras.dcu.ie/14807/1/internet_science_communication.pdf